SELF-DIRECTEDNESS IN NON-FORMAL ONLINE BUSINESS ENGLISH COURSES: ADULT LEARNERS’ PERSPECTIVES: Received: 26th October 2021; Revised: 12th November 2021, 8th January 2022, 25th January 2022; Accepted: 24th February 2022 - Kildė, Laura (PUPIL: International Journal of Teaching, Education and Learning, 2022)
Self-directedness is vital to adult learners as it allows them to stay motivated and achieve effective results while learning online and balancing between family and work. This research aims to determine Lithuanian adult learners perceived self-directedness while learning English for Specific Purposes (ESP) in non-formal online courses. To this end, their approaches towards the factors of self-directedness were investigated. The indicators defined by Khiat (2015), including Goal Setting, Time Management, Procrastination Management, Assignment Preparation, Final Test Preparation, Note-taking Capability, Research Capability, Technical Readiness, Online Class Readiness, and Stress Management were involved in a detailed analysis to establish which variables were the most meaningful ones in terms of learners’ self-directedness. The study revealed that adult students are highly self-directed while learning Business English in non-formal online courses at a language school. The findings confirmed that the application of self-directedness and its development in learning processes leads to higher levels of motivation and successful learning outcomes. Based on the findings, these adult learners’ perspectives could contribute to larger-scale surveys in formal and informal forms of education to enhance learners’ self-directedness and achieve successful learning results.